The Impact of Adjuvant Drug Therapy on Overall Survival in Patients with Clear Cell Renal Cell Carcinoma: A Systematic Review and Meta-Analysis - Lan, Dong; Du, Jianhui; Yuan, Wenqiang; Ying, Qiao; Huang, Guohua; Lan, Jianhua (Urology Journal, 2025)
Purpose: Clear cell renal cell carcinoma (ccRCC), the dominant subtype of renal malignancy, has a rising global incidence and mortality. While surgery is the standard of care for localized cases, adjuvant therapy aims to improve outcomes in high-risk postoperative patients. To quantify the clinical value of adjuvant pharmacotherapy, this systematic review and meta-analysis assesses its effect on overall survival (OS), disease-free survival (DFS), and progression-free survival (PFS) in patients with ccRCC. Materials and Methods: A comprehensive search of the Web of Science, Embase, Cochrane Library, and PubMed databases was conducted for articles published up to October 2024. The search used the English keywords “clear cell renal cell carcinoma,” “adjuvant drug therapy,” and “randomized controlled trials,” combined with a free-word search. Randomized controlled trials (RCTs) assessing the effectiveness of at least one adjuvant drug therapy in patients with ccRCC were included. Results: The meta-analysis showed that adjuvant drug therapy did not result in a statistically significant improvement for OS or PFS compared with the control group. There was also no statistically significant difference in DFS (P > 0.05). This systematic review provides evidence on the impact of adjuvant targeted therapy on OS, DFS, and PFS for patients with clear cell renal cell carcinoma. Conclusion: This study summarizes the effects of adjuvant drug therapy on OS, PFS, and DFS in ccRCC patients. The evidence from this meta-analysis can inform clinical decision-making, support risk stratification strategies, and encourage the integration of OS-driven endpoints in future trial designs, thereby providing valuable data for the treatment of ccRCC.